2015
DOI: 10.5530/pj.2015.4.5
|View full text |Cite
|
Sign up to set email alerts
|

Anxiolytic Potential of Methanol Extract from Ageratum conyzoides Linn Leaves

Abstract: Objective: Ageratum conyzoides Linn. (Asteraceae) has been widely used in African traditional medicine for healing mental and infectious diseases. The present study was designed to scientifically validate the traditional claim of A. conzyoides as anti-anxiety drug and to identify the compound responsible for the anxiolytic effects of A. conzyoides. Method: The methanol extract of A. conzyoides was prepared by soxhlet apparatus. The methanol extract was fractionated into ethylacetate and butanol fractions by li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…Results showed that ethyl acetate fraction was responsible for anxiolytic effects. [66] Wound healing effects, Analgesic activity, Anti-cancer, antiradical scavenging activity and gastric properties, Spasmolytic effects, Gamma radiation effects, Anti-malarial properties, Anticoccidial activity, Schistosomicidal activity, Insecticidal property, Allelopathic property and Antitumour activity. [67][68][69][70] CONCLUSION Scientists needs to the further research on different weeds, one of which is A. conyzoides.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…Results showed that ethyl acetate fraction was responsible for anxiolytic effects. [66] Wound healing effects, Analgesic activity, Anti-cancer, antiradical scavenging activity and gastric properties, Spasmolytic effects, Gamma radiation effects, Anti-malarial properties, Anticoccidial activity, Schistosomicidal activity, Insecticidal property, Allelopathic property and Antitumour activity. [67][68][69][70] CONCLUSION Scientists needs to the further research on different weeds, one of which is A. conyzoides.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…This ensures accurate plant identification, preserves authenticity, and maintains therapeutic efficacy. Such standardization efforts play a crucial role in upholding the quality, safety, and effectiveness of these medicinal plants [4], while also preventing intentional or unintentional adulteration or substitution [5]. Medicinal plants, whether in the form of pure compounds or standardized extracts, offer abundant opportunities for new drug development due to their unparalleled chemical diversity.…”
mentioning
confidence: 99%